Finite Volume Methods for Wave Propagation in Stratified Magneto-Atmospheres (Communications in Computational Physics, 2010)
We present a model for simulating wave propagation in stratified magneto-atmospheres.The model is based on equations of ideal MHD together with gravitationalsource terms. In addition, we present suitable boundary data and steady statesto model wave propagation. A finite volume framework is developed to simulate thewaves. The framework is based on HLL and Roe type approximate Riemann solversfor numerical fluxes, a positivity preserving fractional steps method for discretizingthe source and modified characteristic and Neumann type numerical boundary conditions.Second-order spatial and temporal accuracy is obtained by using an ENO piecewiselinear reconstruction and a stability preserving Runge-Kutta method respectively.The boundary closures are suitably modified to ensure mass balance. The numericalframework is tested on a variety of test problems both for hydrodynamic as well asmagnetohydrodynamic configurations. It is observed that only suitable choices of HLLsolvers for the numerical fluxes and balanced Neumann type boundary closures yieldstable results for numerical wave propagation in the presence of complex magneticfields.